Detection of the types of contaminated fungi of some local and imported nuts and their ability to produce aflatoxin - Kazem, Rafead Jawad (Journal of agricultural, environmental and veterinary sciences, 2017)
This study aimed to detect the types of fungi contaminated for some nuts (seeds) local and imported, and its ability to produce aflatoxin in Al-Shartah and Al- Rifai districts and regions of the two. This study was Accomplished in Shatra General Hospital of the Health Department with the Ministry of Health and the laboratory of fungi in the College of Pharmacy / University of Dhi Qar, for the period from 25/11/2015 until 29/03/2016, this study included collection of samples of nut seeds (sunflower seeds, walnuts seeds, watermelon seeds, Cucurbita seeds, Pistachio seeds) local and imported from vendors in the restrict of Rifai and by 500 g per sample of roasted seeds and stored. it had been going to the places mentioned and collected and recorded the types and quantities of seeds under discussion, were placed in nylon bags (polyethylene) sterile deflated, and put in the refrigerator temperature 5 C °, sample collection process continues until the end of the probation period. Isolated seven fungal genuses were associated with the seeds (sunflower seeds, walnuts seeds, watermelon seeds, Cucurbita seeds, Pistachio seeds)(imported), which were intended for human consumption, as it was the highest rate in the insulation is the fungus Rizhopus spp. (52%) followed by Aspergillus spp. (17%) and then Rhizopus spp. (9%) and Penicillium spp.(6%) , and finally the fungus Rhizocotonia spp.(4%) and Mucur spp.(2%) and Trichderma spp. (1%) , which was a relatively low proportion of isolation.